دور النشاط البدني المصاحب للنظام الغذائي في انقاص الوزن نسب مؤشر كتلة الجسم لدى المراهقين - طواجين, هواري; قاسم, أسامة (My University, 2020)
creasing body mass index ratios Teens. This study aims to know the extent of the role of physical activity accompanying the diet in decreasing adolescent body mass index ratios, and to achieve this goal we have devoted ourselves to the role of physical exercise and diet play an important role in reducing body mass index ratios and protecting it from modern diseases such as obesity, and to confirm the hypothesis We collected a massive collection of similar studies from databases That showed the role of physical activity and diet BMC, Science direct, Pub Med, ASJP Among the most important things that we have come up with is the effective role of physical and athletic sports accompanying the diet in decreasing body mass index ratios and protecting it from modern diseases.
MAPA2020-07
Keywords: النشاط البدلش الرياضي; لنظام الغذائي; نسب مؤشر; الوزن الزائد